PERHITUNGAN KOMPRESI TRANSMISI (CONTINUOUSLY VARIABLE TRANSMISSION) PADA SEPEDA MOTOR MATIC 150 CC - Bagas Imam Priambodo; Hilman Sholih; Firmansyah Azharul (JTTM : Jurnal Terapan Teknik Mesin, 2021)
CVT system (Continuously Variable Transmission) is a transmission system that uses a pulley and belt system, instead of using gears. The components of a continuously variable transmission are studied through this analysis, including how CVT functions. The object of this research was to decide the centrifugal force measurement. Usage of real data on motorized vehicles using CVT in this estimate. The object of this analysis was to decide the centrifugal force measurement. Usage of real motorized vehicle data using CVT in this estimation. The engine-generated details and the distance or displacement that takes place in the drive pulley. There is a top speed of 8500 RPM from the value received. 10.68984 Nm torque, kW 7.93275154, 60.6 Nm centrifugal force, displacement: 24.6 mm